Clinical and Pathological Characteristics of Patients With Nonproteinuric Diabetic Nephropathy - Chang, Dong-Yuan; Li, Meng-Rui; Yu, Xiao-Juan; Wang, Su-Xia; Chen, Min; Zhao, Ming-Hui (Frontiers in Endocrinology, 2021)
Introduction: As the most common complication of diabetes mellitus(DM), diabetic nephropathy (DN) was initially considered to begin with proteinuria preceding the progression of renal insufficiency. This clinical paradigm has been questioned in the late decades, as many DM patients without proteinuria have progressive renal insufficiency. However, the characteristics of nonproteinuric DN were not fully clear yet. Patients and methods: A total of 390 patients with renal biopsy-proven DN in our center were retrospectively recruited in the current study. Clinical and histopathological data of the patients were analyzed. We used propensity score-matching methods to address the imbalance of age, sex, and diabetes duration for comparative analyses. Results: Among all the renal biopsy-proven DN patients with renal biopsy proven DN, 18 patients were classified as nonproteinuric DN. Compared with 36 propensity score-matched proteinuric DN patients, diabetic retinopathy (DR) was less frequent in nonproteinuric DN patients (38.9% vs. 66.4%, p<0.05). During the follow-up of 24.0 (12.0–42.0) months, the probability of developing the end-stage renal disease (ESRD) was significantly lower in nonproteinuric DN patients than in proteinuric ones in both the propensity score-matched cohort and overall cohort (log-rank test, p<0.001 and p<0.001, respectively). Conclusions: Compared with proteinuric DN patients, DR was less frequent in nonproteinuric DN patients. Nonproteinuric DN patients had better renal outcomes than proteinuric DN patients.